Public Participation of Sustainable Tourism Development in The Coastal Area of Kili Kili Park In Wonocoyo Village, Panggul Subdistrict, Trenggalek District - Yusup Saktiawan; Bagyo Yanuwiadi; Aminudin Afandhi (The Indonesian Green Technology Journal, 2018)
The objectives of this research are focusing on three points: 1) to analyze the considerable factors that underpin the development of sustainable tourism in coastal area of Kili Kili Park in Wonocoyo village, Panggul subdistrict, Trenggalek district; 2) to analyze forms and types of public participation in developing sustainable tourism in coastal area of Kili Kili Park; and 3) to formulate the public strategy for sustainable tourism development in coastal areas of Kili Kili Park. In this research, the techniques of data retrieval use interview, observation, and documentation and triangulation. Wonocoyo village located in Panggul subdistrict, Trenggalek, is as the object of the research. The results of the study show that if environmental factors are the most influencing factors of sustainable development with a score of 3.87, the level of public participation in coastal development is still lacking with a score of 1354. Strategies that can be used to increase tourists are to enhance and strengthen the promotions, the tourism facilities and the tourist attractions.Key words: Coastal Area, Public Participation, Panggul District, Sustainable Tourism Development, Wonocoyo Village